Awareness of patients with acute coronary syndrome about risk factors and symptoms of myocardial infarction - D. N. Brylyakova; A. A. Belopolskaya; L. A. Sorokin; G. A. Kukharchik (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
We identified insufficient awareness of patients about risk factor and symptoms of myocardial infarction in both groups. Respondents without acute coronary syndrome were better informed and had fewer modifiable risk factors. Low awareness of risk factors for myocardial infarction leads to their inadequate correction. In most cases, insufficient knowledge of symptoms causes delays in the patient 's decision to see a doctor, and, therefore, delays in qualified care.